Investigating Dietary Variation With Burial Ritual in Iron Age Hampshire: An Isotopic Comparison of Suddern Farm Cemetery and Danebury Hillfort Pit Burials. Issue 3 (2nd July 2013) - Stevens, Rhiannon E.; Lightfoot, Emma; Hamilton, Julie; Cunliffe, Barry; Hedges, Robert E.M.
Summary The formal Iron Age cemetery at Suddern Farm, located near Danebury hillfort, provides a unique opportunity to investigate whether differences in burial tradition and ritual behaviour seen at the two sites are linked to access to food resources during life. We measured the carbon and nitrogen isotopic ratios of 40 humans from Suddern Farm and compared this information to previously published faunal data from the site and human isotopic data from Danebury. Despite substantial variation in the faunal isotope signatures, the adult humans have notably homogeneous isotopic results, which are very similar to those at Danebury. This indicates that they had similar access to dietary resources, and supports other evidence for the interdependence of sites with regard to their farming practices. Any social practices that define groups within Hampshire Iron Age society at these sites do not seem to have had any detectable influence on diet.